Relationship between Success Rate of ARV Tablet Consumption in Pregnant Women with HIV at Ir. Soekarno Regional Hospital, Morotai Island - Intan Wulandary; Anik Sri Purwanti; Widia Shofa Ilmiah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Human Immunodeficiency Virus (HIV) infection in pregnant women is a serious concern in efforts to prevent mother-to-child transmission (PMTCT). Regular consumption of Antiretroviral (ARV) tablets is very important to suppress viral load and increase treatment success. However, the level of compliance of pregnant women in consuming ARV is still a challenge in various health facilities, including at RSUD Ir. Soekarno Morotai Island. This study aims to analyze the relationship between the level of success of ARV tablet consumption and pregnant women infected with HIV at RSUD Ir. Soekarno Morotai Island. This study used an analytical design with a cross-sectional approach. The number of respondents was 16 pregnant women with HIV who were registered in the ARV therapy program at RSUD Ir. Soekarno Morotai Island. Data were collected through observation of ARV consumption compliance and interviews using structured questionnaires. Data analysis was carried out using the Wilcoxon test to see the relationship between the success of ARV consumption and maternal health status. The results of the study showed that there was a significant relationship between the level of success of ARV tablet consumption and the health conditions of pregnant women with HIV, with a p-value of 0.001 (<0.05). A total of 15 respondents (93.8%) who were compliant in consuming ARV experienced improvements in health status, while 1 respondent (6.2%) with low compliance showed less than optimal health outcomes. The success of ARV consumption plays an important role in improving the health of pregnant women with HIV, as well as contributing to reducing the risk of HIV transmission from mother to child. Therefore, compliance in consuming ARV needs to be continuously improved through education and support from health workers. Health workers are expected to be more active in providing education and assistance to pregnant women with HIV so that they are more compliant in consuming ARV. In addition, there needs to be a periodic monitoring and evaluation program to ensure the effectiveness of ARV therapy in preventing HIV transmission from mother to child.